Rogue state a guide to the world's only superpower - Blum, William (Monroe Common Courage Press, 2000)
After reading Rogue State, it is impossible to hang fast to the comforting illusion that the American way is some kind of enlightenment.Will SelfA book of charges to be tied to a paving stone and thrown at the men in Washington.Independent on SundayRogue State and its author came to sudden international attention when Osama Bin Laden quoted the book publicly in January 2006, propelling the book to the top of the bestseller charts in a matter of hours. It is an essential guide to the crimes and misdemeanours of the worlds only superpower.
Includes bibliographical references (p. [274-304) and index.
Keywords: Intervention (International law)